Speech Language Therapy for Children with ASD and Their Families during the Covid-19 Pandemic: Considerations about Professional Training and Service Delivery on a Majority Country - Fernanda Dreux M. Fernandes; Ingrid Ya I. Sun; Beatriz Ferreira Rodrigues; Cinthia Parada Cabral; Clarice Tosetto; Letícia Segeren (Highlights on Medicine and Medical Research Vol. 4, 2021)
The need for health professionals to embrace new technologies and develop competencies to use them is made clear by the increase in the demands for health services available to children with Autism Spectrum Disorders (ASD) and their families. The COVID-19 pandemic highlighted the urgency to consider all possibilities of maintaining and improving the services available to this population. It also became clear that the professional training of speech language pathologists (SLP) should include the use of teleheath technologies in professional practice. This chapter will discuss two studies. The first one deals with the impact of telepractice in different levels of professional education in Speech-Language Pathology. The results indicate that most students reported uncertainty and despair regarding the use of digital technologies in the learning and intervention processes. However, after a brief period they consider that both learning and intervention processes were productive and presented positive results. The second study presents details about a period of intervention that used different technologies available to families of children with ASD. We conclude that telepractice is an important alternative to the professional training of speech-language pathologists and on service delivery but do not exclude face-to-face experiences.